Letter (copy) : Foodstuffs for Spain - Tewson, Vincent
029-0040-001 HVT/AC/164. Secretary's. 14th January, 1938. Mr. W. Schevenels, The International Federation of Trade Unions, 9 Avenue D'Orsay, PARIS, VIIe. Dear Schevenels, Foodstuffs for Spain. I have again referred to your letter of the 8th instant and note that you are awaiting our final information regarding the probable date of arrival of the consignment of goods sent by the s.s. HARTBRIDGE. You will notice that I stated in my letter to you of the 5th instant that the boat had arrived at Algeria two days previously, and that the goods might have already been transhipped. We have no definite information here, but I think the goods must have arrived in Barcelona by now. If you have not already done so perhaps you would get into touch with your contact in Barcelona immediately on this matter, Yours sincerely, Assistant Secretary. 292/946/29/40